CAD-FEA modeling and analysis of different full crown monolithic restorations - Dal Piva, Amanda Maria de Oliveira [UNESP] (2018)
Objectives: To investigate the influence of different materials for monolithic full posterior crowns using 3D-Finite Element Analysis (FEA). Methods: Twelve (12) 3D models of adhesively-restored teeth with different crowns according to the material and its elastic modulus were analysed: Acrylic resin, Polyetheretherketone, Composite resin, Hybrid ceramic, pressable and machinable Zirconia reinforced lithium silicate, Feldspathic, Lithium disilicate, Gold alloy, Cobalt–Chromium alloy (Co–Cr), Zirconia tetragonal partially stabilized with yttria, and Alumina. All materials were assumed to behave elastically throughout the entire deformation. Results in restoration and cementing line were obtained using maximum principal stress. In addition, maximum shear stress criteria was used for the cementing line. Results: Restorative materials with higher elastic modulus present higher stress concentration inside the crown, mainly tensile stress on an intaglio surface. On the other hand, materials with lower elastic modulus allow stress passage for cement, increasing shear stress on this layer. Stiffer materials promote higher stress peak values. Significance: Materials with higher elastic modulus such as Co–Cr, zirconia and alumina enable higher tensile stress concentration on the crown intaglio surface and higher shear stress on the cement layer, facilitating crown debonding.